2012
DOI: 10.1021/nn2047185
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselective Photodeoxidization of Graphene Oxide Using Sterically Hindered Amines as Catalyst: Synthesis and Applications

Abstract: We report a green and efficient method for chemoselective deoxidization of graphene oxide via the ultraviolet irradiation catalyzed with 2,2,6,6-tetramethyl-4-piperidinol. While the sp(2)-hybridized oxygen functional groups are removed after the reduction, the epoxy and hydroxyl groups are retained in the chemoselectively reduced graphene oxide (CrGO). The obtained CrGO nanosheets exhibit the high solubility and excellent electronic stability, which allows for the fabrication of thin film devices through a sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
72
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 56 publications
2
72
0
2
Order By: Relevance
“…The formed GO film was crackless with some wrinkles (Fig. S6) like the common graphen-based film3651. The g-C 3 N 4 -NSs film was formed on GO layer through the sprayed fog of g-C 3 N 4 -NSs aqueous solution in virtue of a commercial humidifier (step 4).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The formed GO film was crackless with some wrinkles (Fig. S6) like the common graphen-based film3651. The g-C 3 N 4 -NSs film was formed on GO layer through the sprayed fog of g-C 3 N 4 -NSs aqueous solution in virtue of a commercial humidifier (step 4).…”
Section: Resultsmentioning
confidence: 97%
“…For instance, some promising memory diodes based on graphene oxide (GO) film as the active insulator layer have been presented3435. However, the device reliability is an inevitable issue due to the unstability of active oxygen functional groups on GO3637. Meanwhile, GO layers have to be coupled with specific metal electrodes to achieve the rewritable function and enhance the ON/OFF ratio38.…”
mentioning
confidence: 99%
“…Indeed, Bagri et al have studied theoretically and experimentally the reduction mechanism of chemically derived GO during annealing, and the results show that the -OH group desorbs at low temperature. 39 In addition, they observed that the >C]O oxygen functional group is more stable than the other oxygen have shown that GO can be selectively photoreduced by using sterically hindered amines as a catalyst, 43 indicating that the reduction mechanism of oxygen functional groups is dependent on the reaction environment. The reported results corroborate with our obtained results pertaining to the stability of the >C] O and C-O-C functional groups on the surface of rGO, even up to 400 C. It is also believed that the removal of -OH and -COOH oxygen functional groups is possible by photocatalytic reduction, as the reduction occurs through the transfer of electrons from the photocatalyst to these oxygen sites.…”
Section: Resultsmentioning
confidence: 99%
“…X‐ray photoemission spectroscopy (XPS) is a powerful tool to characterize graphene derivatives and provides the composition and percentage of the functional groups present on the surface of the graphene oxide and reduced graphene oxide , . In the current case, XPS survey was used to confirm the reduction extent estimated by FT‐IR.…”
Section: Resultsmentioning
confidence: 99%